Pengaruh Persepsi Harga, Kualitas Pelayanan dan Citra Merek terhadap Kepuasan Pelanggan - Yusuf Suhardi; Agustian Burda; Achmad Ridho; Zulkarnaini Zulkarnaini; Arya Darmawan (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
This study aims to determine and analyze the effect of price perception, service quality and brand image on customer satisfaction. This research is motivated by the tight competition in the duck culinary business among the duck restorers. The research method used is a survey method, using a questionnaire as a data collection tool. The population in this study were consumers of the Bebek Oke restaurant. The sample used for this study were 126 consumers. Based on the results of the study, there was no effect of price perception on customer satisfaction. There is a significant positive effect of service quality on customer satisfaction and there is a significant positive effect of brand image on customer satisfaction. Simultaneously perception of price, service quality and brand image have a positive effect on customer satisfaction at Bebek Oke Pramuka restaurant in Jakarta.